Adjuvant therapy in renal cell carcinoma: Current knowledges and future perspectives. (June 2021) - Larroquette, Mathieu; Peyraud, Florent; Domblides, Charlotte; Lefort, Félix; Bernhard, Jean-Christophe; Ravaud, Alain; Gross-Goupil, Marine
Highlights: While approximately 70% of cases of renal cell carcinoma (RCC) are diagnosed at non-metastatic stage, effective adjuvant treatments are urgently needed to reduce the risk of recurrence. Identification of patients with high risk of relapse is challenging to tailor postoperative management. To date, almost all of the tested adjuvant agents, including antiangiogenic tyrosine-kinase inhibitor, have failed to demonstrate any benefit. With new insights providing in the domain of immunotherapy, the landscape of perioperative management of RCC continues to evolve. Abstract: While many patients with non-metastatic renal cell carcinoma (RCC) can be cured with surgery alone, upward of 40% of patients recur in a short delay, raising the question of additional perioperative treatments. To address this clinical need, multiple trials have investigated the addition of systemic therapy after surgery in localized or locally advanced RCC. However, adjuvant systemic therapies in the past decades have provided disappointing results with only one positive study of antiangiogenic treatments. Debatable clinical benefit of adjuvant antiangiogenic tyrosine kinase inhibitors (TKIs) therapy at cost of high adverse event profiles have paved the way for development of alternative perioperative strategies, such as immune checkpoint inhibitors (ICIs). Further investigation into combination therapies with immunotherapy, neoadjuvant approaches and patient selection will be key to determining optimal adjuvant therapy regimens to improve outcomes and increase cure rates for patients with non-metastatic RCC. In this review, we extensively present the strong and weakness of the five adjuvant antiangiogenic TKI trials, highlight the main differences and discuss about the reasons of failure. We also expose the current ongoing clinical trials in the perioperative setting and provide new insights concerning the evolving landscape of the management of non-metastatic RCC.